The epistemic dimension in discourse analysis in a physicochemical class - Guillermo Cutrera; Silvia Stipcich; Ricardo Chrobak (Universidad de Granada, 2013)
The distinction between knowledge in sciences and knowledge of sciences, highlights the importance of knowledge about different aspects of the scientific activity. This double dimension of the school content is recovered through the different high school curriculum reforms in different countries. In this work we analyze how a prospective teacher of chemistry, conveys different notions on the nature of science through his discourse. We propose and discuss a categorization of those notions and the process of analysis is synthesized through the use of conceptual maps.